Date Palm Fruits as a Potential Source of Functional Dietary Fiber: A Review - Jiménez-Araujo, Ana; Sindic, Marianne; Mrabet, Abdessalem; Rodríguez-Gutiérrez, Guillermo; Hammadi, Hamza (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2019)
Date palm fruits and their seeds are excellent sources of dietary fiber (DF). Date fruits contain 8.1–12.7 % Total DFs (of which 84–94 % is insoluble and 6–16 % soluble DF) and is very rich in phenolic antioxidants (1–2 %). Date fruit fibers are composed of cellulose and NSP. Moreover, date DF has important functional properties, such as water-holding capacity and oil-holding capacity. Date seeds contain about 15 % fiber, characterized by a high level of water-insoluble mannan fibers. It has been suggested that date fruits and seeds can be exploited in some food applications. In order to improve fiber yields, pretreatment procedures can be applied, which give excellent results in the case of date palm fibers. Date fruits are widely available in the global market, but there is still room for improvement, particularly in the revalorization of date processing waste, and secondary cultivars. The incorporation of date fruits and seeds as food ingredients would promote the presence of dates in the modern's consumer shopping basket. Present knowledge about different aspects of date DF, and suitable extraction methods and applications of date fiber (flesh and seed), will be the focus of this report.